Knockdown of embryonic myosin heavy chain reveals an essential role in the morphology and function of the developing heart - Rutland, Catrin S.; Polo-Parada, Luis; Ehler, Elisabeth; Alibhai, Aziza; Thorpe, Aaran; Suren, Suganthi; Emes, Richard D.; Patel, Bhakti; Loughna, Siobhan (Company of Biologists, 2011)
The expression and function of embryonic myosin heavy chain (eMYH) has not been investigated within the early developing heart. This is despite the knowledge that other structural proteins, such as alpha and beta myosin heavy chains and cardiac alpha actin, play crucial roles in atrial septal development and cardiac function. Most cases of atrial septal defects and cardiomyopathy are not associated with a known causative gene, suggesting that further analysis into candidate genes is required. Expression studies localised eMYH in the developing chick heart. eMYH knockdown was achieved using morpholinos in a temporal manner and functional studies were carried out using electrical and calcium signalling methodologies. Knockdown in the early embryo led to abnormal atrial septal development and heart enlargement. Intriguingly, action potentials of the eMYH knockdown hearts were abnormal in comparison with the alpha and beta myosin heavy chain knockdowns and controls. Although myofibrillogenesis appeared normal, in knockdown hearts the tissue integrity was affected owing to apparent focal points of myocyte loss and an increase in cell death. An expression profile of human skeletal myosin heavy chain genes suggests that human myosin heavy chain 3 is the functional homologue of the chick eMYH gene. These data provide compelling evidence that eMYH plays a crucial role in important processes in the early developing heart and, hence, is a candidate causative gene for atrial septal defects and cardiomyopathy.